2013
DOI: 10.1007/s12519-013-0433-1
|View full text |Cite
|
Sign up to set email alerts
|

Urinary tract infections in neonates with jaundice in their first two weeks of life

Abstract: UTI should be investigated in neonates with hyperbilirubinemia of unknown etiology in the first two weeks of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
1
2

Year Published

2015
2015
2025
2025

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 9 publications
5
31
1
2
Order By: Relevance
“…UTIs are well-known to cause prolonged jaundice and are investigated routinely. On the other hand, some authors suggest investigating UTI also in the neonates requiring treatment for pathologic indirect hyperbilirubinaemia, 3,4,6,7,9 while some do not. 5,8 Therefore, it is controversial to look for UTI in these patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…UTIs are well-known to cause prolonged jaundice and are investigated routinely. On the other hand, some authors suggest investigating UTI also in the neonates requiring treatment for pathologic indirect hyperbilirubinaemia, 3,4,6,7,9 while some do not. 5,8 Therefore, it is controversial to look for UTI in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…4,11 Two other studies from Turkey examined UTI prevalence in <2-week-old newborns with asymptomatic, unexplained indirect hyperbilirubinemia. 6,9 Bilgen et al 6 examined 102 patients and reported UTI as 8%. Most recently, Mutlu et al 9 studied 104 patients and reported UTI as 18%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3538 Onset of jaundice after 8 days of life in particular has been associated with UTI. 37,39 Twenty-eight of 30 infants with UTI-induced jaundice had indirect hyperbilirubinemia, and about half of them had renal cortical changes on DMSA scan.…”
Section: Clinical Correlationsmentioning
confidence: 99%